Molecular Characterization of Extended-Spectrum β-Lactamase–Producing Escherichia coli and Klebsiella pneumoniae Among the Pediatric Population in Qatar - Perez-Lopez, Andres; Sundararaju, Sathyavathi; Al-Mana, Hassan; Tsui, Kin Ming; Hasan, Mohammad Rubayet; Suleiman, Mohammed; Janahi, Mohammed; Al Maslamani, Eman; Tang, Patrick (Frontiers in Microbiology, 2020)
Introduction: Although extended-spectrum β-lactamase (ESBL)-producing Enterobacterales are a public health problem in the Arabian Peninsula, data on the molecular characteristic of their antimicrobial resistance determinants in children is limited. Aim: To determine the molecular characteristics of ESBL-producing Escherichia coli and Klebsiella pneumoniae in the pediatric population of Qatar. Methods: Whole-genome sequencing (WGS) was performed on ESBL-producing E. coli and K. pneumoniae isolates recovered from screening and clinical specimens from pediatric patients at Sidra Medicine in Doha from January to December 2018. Results: A total of 327 ESBL producers were sequenced: 254 E. coli and 73 K. pneumoniae. Non-susceptibility rates to non-beta-lactam antibiotics for both species were: 18.1% and 30.1% for gentamicin, 0.8% and 4.1% for amikacin, 41.3% and 41.1% for ciprofloxacin, and 65.8% and 76.1% for co-trimoxazole. The most common sequence types (ST) were ST131 (16.9%), ST38 and ST10 (8.2 % each) in E. coli and ST307 (9.7%), ST45 and ST268 (6.9% each) in K. pneumoniae. CTX-M type ESBL were found in all but one isolate, with CTX-M-15 accounting for 87.8%. Among other beta lactamases, TEM-1B and OXA-1 were co-produced in 41% and 19.6% of isolates. The most common plasmid-mediated quinolone resistance genes co-carried were qnr A/B/E/S (45.3%). Ninety percent of gentamicin non-susceptible isolates harbored genes encoding AAC(3) enzymes, mainly aac(3)-IIa. Only 2 of 57 isolates harboring aac(6’)-Ib-cr were non-susceptible to amikacin. Chromosomal mutations in genes encoding DNA gyrase and topoisomerase IV enzymes were detected in 96.2% fluoroquinolone-non-susceptible E. coli and 26.7% fluoroquinolone-non-susceptible K. pneumoniae. Conclusions: Our data show that CTX-M enzymes are largely the most prevalent ESBLs in children in Qatar with a predominance of CTX-M-15. Carbapenem-sparing options to treat ESBL infections are limited given the frequent co-production of OXA-1 and TEM-1B enzymes and co-resistance to antibiotic classes other than β-lactams.